Floccillation: A Diagnostic Clue to Delirium - Miki Sato; So Sakamoto; Taku Harada; Hidehiro Ozawa; Mori Nakai (Annals of Internal Medicine: Clinical Cases)
Delirium is common among elderly individuals. Patient interview remains the main diagnostic tool, although accurate information can be difficult to obtain in patients with communication disorders. Here, we describe the presence of new-onset floccillation as a specific sign of new-onset delirium in a 91-year-old man with recurrent acute stroke in the right middle cerebral artery territory. Therefore, floccillation may be useful to diagnose early-onset hypoactive or hyperactive delirium.